The Oxford handbook of digital ethics - Véliz, Carissa (New York : Oxford University Press, 2023)
"The Oxford Handbook of Digital Ethics is a lively and authoritative guide to ethical issues related to digital technologies, with a special emphasis on AI. Philosophers with a wide range of expertise cover thirty-seven topics: from the right to have access to internet, to trolling and online shaming, speech on social media, fake news, sex robots and dating online, persuasive technology, value alignment, algorithmic bias, predictive policing, price discrimination online, medical AI, privacy and surveillance, automating democracy, the future of work, and AI and existential risk, among others. Each chapter gives a rigorous map of the ethical terrain, engaging critically with the most notable work in the area, and pointing directions for future research"-- "The Oxford Handbook of Digital Ethics is a lively and authoritative guide to ethical issues related to digital technologies, with a special emphasis on AI. Philosophers with a wide range of expertise cover thirty-seven topics: from the right to have access to internet, to trolling and online shaming, speech on social media, fake news, sex robots and dating online, persuasive technology, value alignment, algorithmic bias, predictive policing, price discrimination online, medical AI, privacy and surveillance, automating democracy, the future of work, and AI and existential risk, among others. Each chapter gives a rigorous map of the ethical terrain, engaging critically with the most notable work in the area, and pointing directions for future research"--